2021
DOI: 10.1016/j.ajhg.2021.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Phenome risk classification enables phenotypic imputation and gene discovery in developmental stuttering

Abstract: Developmental stuttering is a speech disorder characterized by disruption in the forward movement of speech. This disruption includes part-word and single-syllable repetitions, prolongations, and involuntary tension that blocks syllables and words, and the disorder has a life-time prevalence of 6-12%. Within Vanderbilt's electronic health record (EHR)-linked biorepository (BioVU), only 142 individuals out of 92,762 participants (0.15%) are identified with diagnostic ICD9/10 codes, suggesting a large portion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
(99 reference statements)
0
15
0
Order By: Relevance
“… 49 , 50 The electronic health record at Vanderbilt University Medical Center offers de-identified demographic data, clinical notes, electronic orders, laboratory measurements, ICD-9 CM/ICD-10 disease diagnosis codes, and CPT codes. Using electronic health records, individuals with diagnoses of developmental, speech, or language disorders as identified via ICD-9 and ICD-10 codes ( Table S1 ) or a phenome risk classifier, 51 52 and individuals under age 18 years were excluded as potential control subjects. To select ancestry-matched control subjects, we calculated eigenvectors and eigenvalues through principal component analysis (PCA) run on PLINKv.1.90.…”
Section: Methodsmentioning
confidence: 99%
“… 49 , 50 The electronic health record at Vanderbilt University Medical Center offers de-identified demographic data, clinical notes, electronic orders, laboratory measurements, ICD-9 CM/ICD-10 disease diagnosis codes, and CPT codes. Using electronic health records, individuals with diagnoses of developmental, speech, or language disorders as identified via ICD-9 and ICD-10 codes ( Table S1 ) or a phenome risk classifier, 51 52 and individuals under age 18 years were excluded as potential control subjects. To select ancestry-matched control subjects, we calculated eigenvectors and eigenvalues through principal component analysis (PCA) run on PLINKv.1.90.…”
Section: Methodsmentioning
confidence: 99%
“…Phecodes are a representation of clinical phenotypes that can be used to identify cases and controls based on the mapping of International Classification of Diseases codes present in individuals' EMR (Bastarache, 2021). The classifier enabled identification of 9239 individuals predicted to have stammering from their research biorepository, empowering a common variant genome‐wide association study that identified two loci (Shaw et al, 2021).…”
Section: The Challenge Of Representing Important Absent Phenotypesmentioning
confidence: 99%
“…However, Pruett et al (2021) found it to be under-reported in EMR billing code data from the Vanderbilt University Medical Center, given the 1%−3% prevalence in the general population. We too have found empowering a common variant genome-wide association study that identified two loci (Shaw et al, 2021).…”
Section: Domain-specific Biomedical Ontologies Can Be Improved Throug...mentioning
confidence: 99%
“…The goal of extending these lines of research to other speech, language, and reading traits highlights the need for coordinated efforts toward collecting and meta-analyzing largescale data in cohorts that have been able to link language-related traits to genotypes. [e.g., GenLang consortium (genlang.org): Eising et al, 2021, BioRXiv, Lancaster et al, in prep.; International Stuttering Project (theinternationalstutteringproject.com): Polikowsky et al, 2021;Shaw et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…[e.g., GenLang consortium ( genlang.org ): Eising et al, 2021 , BioRXiv , Lancaster et al, in prep. ; International Stuttering Project ( theinternationalstutteringproject.com ): Polikowsky et al, 2021 ; Shaw et al, 2021 ].…”
Section: Introductionmentioning
confidence: 99%